The Impact of the Problem Solving Strategy on Acquiring Technology Concepts in the Computer Science of Ninth Grade Students in Jordan - Aldmour, Rowaydah Faiq Hammad (Journal of Educational and Psychological Sciences, 2019)
The purpose of this study was inquiring The Impact of the Problem Solving Strategy on Acquiring Technology Concepts in the Computer Science of Ninth Grade Students in Jordan.To achieve goals of this study, a test has been developed to observe the Technology Concepts. The researcher adopted a quasi-experimental approach in which the experimental group consisting of (30) students was taught in accordance with Problem Solving Strategy. At the same time, the controlled group consisting of (30 students) was taught in the traditional way.The tests and the motive measuring was applied prior and post- teaching on both groups. The Analysis of Covariance results (ANCOVA) indicated a significant difference at (α≤0.05) between the two groups, which is attributed to the Problem Solving Strategy, in developing the Acquiring Concepts in Computer Science, of Computer Science Education Course for the experimental group. The results also indicated variation in the performance of (the experimental group) students in the posttest of the Problem Solving Strategy (in developing the Technology Concepts.The study recommended introducing the Problem Solving Strategy in the teaching of Computer Science Education Course, and conducting other similar studies in different educational stages.
Keywords: Problem Solving Strategy; Technology Concepts; Computer Science Education